Using health action process approach to determine diet adherence among patients with Type 2 diabetes - Soheila Ranjbaran; Davoud Shojaeizadeh; Tahereh Dehdari; Mehdi Yaseri; Elham Shakibazadeh (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Diet adherence may cause diabetes complications to be diminished. OBJECTIVES: This study aimed at identifying determinants of diet adherence among patients with Type 2 diabetes based on the health action process approach (HAPA). METHODS: In this cross-sectional study, 734 patients with Type 2 diabetes, attending to South Tehran health centers, were recruited during June-December 2018. The dietary regimen scale (nine items) and a researcher-designed questionnaire consisting of HAPA constructs were used to gather the data. Data were analyzed using the Mann-Whitney test, Pearson Chi-squared test, Fisher's exact test, and linear regression test. All statistical tests were assessed using SPSS (IBM Corp. Released 2017. IBM SPSS Statistics for Windows, Version 25.0. Armonk, NY, USA: IBM Corp.). RESULTS: The level of nonadherence to diet was 91.1%. Diet adherence was significantly associated with family income (P = 0.005), level of education (P < 0.001), and age (P = 0.009). The linear regression showed that 55% of the variance of diet adherence was determined by HAPA variables. Diet adherence was associated with intention (P < 0.001), action planning (P = 0.005), and barriers (P = 0.003). CONCLUSION: Most of the patients did not adhere to their diet. Appropriate programs should be designed to promote diet adherence among the patients, especially those with low literacy and patients living in poor communities.